Pembuatan Tapal Batas di Pekon MalayaKecamatan Lemong, Kabupaten Pesisir Barat, Lampung - Bindar, Muhammad Abdul Mubdi; Kurniawan , Jatmiko; Fandi , Oki Okta; Manullang , Roida; Fergusta , Wilibrordus Bima Digdya; Achmad , Feerzet (Journal of Industrial Community Empowerment, 2024)
The certainty of village boundaries is important in the management of rural areas. The lack of clarity in the boundaries between Pekon Malaya and Pekon Bambang in Lemong District, Pesisir Barat Regency, Lampung, has led to the need to establish clear boundaries between the two villages. This study aims to construct physical boundary markers between the two pekons to avoid territorial conflicts. The methods used include inter-village consultation, design, and physical construction of the boundary markers. The main result of this study is the creation of clear physical boundary markers between Pekon Malaya and Pekon Bambang, which can be used as a reference in resolving village boundary issues in the future. The conclusion of this study is that the construction of physical boundary markers can be an effective solution to address the problem of unclear village boundaries.